ANALISIS PRODUKTIVITAS MENGGUNAKAN METODE OBJECTIVE MATRIX (OMAX) PADA INDUSTRI GALANGAN KAPAL DI SURABAYA - Dinda Aulia Putri Athallah; Renanda Nia Rachmadita; Devina Puspita Sari (Proceeding Maritime Business Management Conference, 2023)
For more than 20 years, one of the shipyard companies in Surabaya (PGS) has experienced the ups and downsof the shipyard business. Based on the number of ships repaired and the number of plates used by PGS per month in 2022, it is still fluctuating, indicating an inconsistency in the process of ship repair or input. The purpose of this study is to analyze the productivity value of the production division and analyze the factors that cause changes in productivity per month. From the results of calculating 4 productivity ratios using the objective matrix (OMAX) method and analyzing them with a traffic light system (TLS), with a total of 2 greenindicators, yellow with 22 and 24 with more red indicators indicating the need for improvement. In a comparison of productivity with the productivity index (IP), there were negative final results for six months (February (-5.7), March (-10.3), April (-2.0), May (-12.0) , September (-10.3), and November (-22.3)), a negative result means below standard or average. Then look for the root of the problem related to the cause of the ratio notreaching the target with a fishbone diagram.